2011
DOI: 10.1071/py10013
|View full text |Cite
|
Sign up to set email alerts
|

Integration of complementary and alternative medicine information and advice in chronic disease management guidelines

Abstract: The growing evidence on the benefits and risks of complementary and alternative medicine (CAM) and its high rate of use (69% of Australians) - particularly for chronic or recurrent conditions - means increasing attention on CAM. However, few people disclose CAM use to their GP, and health professionals tend to inadequately discuss CAM-related issues with their patients, partly due to insufficient knowledge. As clinical and non-clinical chronic condition management guidelines are a means to educate primary heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…25 Furthermore, they value women having opportunities to make decisions, even if they do not want to pursue them. 25 In line with other research exploring the attitudes of doctors 36 and midwives, 28 our data indicates that CAM is not a key concern and other topics deemed more essential often take precedence. Midwives' attitudes reflected the assertion of Leap and Pairman 26 that persuading the woman to consider various options is a legitimate part of midwifery practice and central to working in partnership.…”
Section: Discussionsupporting
confidence: 88%
“…25 Furthermore, they value women having opportunities to make decisions, even if they do not want to pursue them. 25 In line with other research exploring the attitudes of doctors 36 and midwives, 28 our data indicates that CAM is not a key concern and other topics deemed more essential often take precedence. Midwives' attitudes reflected the assertion of Leap and Pairman 26 that persuading the woman to consider various options is a legitimate part of midwifery practice and central to working in partnership.…”
Section: Discussionsupporting
confidence: 88%
“…The arrays were pre-processed and normalized using R (22), the bead array (23), and Bioconductor (24) packages. Between arrays, quintile was normalized using the Lumi package (25).…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have examined CAM guidelines. Content analysis of 10 guidelines on cardiovascular disease and type II diabetes revealed that CAM-relevant information was brief, in some cases unclear, inconclusive and lacking in direction for health care professionals [34]. Analysis of 65 National Institute for Health and Clinical Excellence guidelines available in 2009 found that, among 17 guidelines that mentioned CAM, it was not clinically relevant to most; in 14 of 48 guidelines that did not mention CAM, available evidence on the safety and effectiveness of relevant CAM therapies had not been included [35].…”
Section: Introductionmentioning
confidence: 99%